Patterns of Gender Equitable Attitudes and Behaviors Among Young Men: Relationships With Violence Perpetration and Masculinity Ideologies - Casey, Erin A. (Violence against women, 2024)
This study used latent profile analysis with data from 481 U.S. men to examine patterns of men's attitudes toward gender equity and their engagement in gender-equitable (GE) behaviors. Five resulting profiles included groups with (a) high endorsement of both GE attitudes and behaviors, (b) low endorsement of both, (c) mid-range endorsement of both, (d) strong endorsement of GE attitudes, but low engagement in action, and (e) low endorsement of GE attitudes but high participation in GE behavior. Worryingly, this last group reported higher rates of violence perpetration than other groups, while simultaneously reporting higher rates of participation in gender-based violence prevention actions.